2008
DOI: 10.1007/s10545-008-0899-5
|View full text |Cite
|
Sign up to set email alerts
|

Congenital generalized lipodystrophy in an Indian patient with a novel mutation in BSCL2 gene

Abstract: Congenital generalized lipodystrophy (CGL) is an autosomal recessive metabolic syndrome with involvement of multiple organs. Mutations in BSCL2 are known to be associated with a severe form of CGL and mental retardation (MR). The genetic heterogeneity in CGL patients is accompanied by phenotypic heterogeneity in different ethnic groups. Studies in the Indian context are very few in this regard. We report here a detailed clinical analysis of a CGL case from infancy to adult hood. Interestingly, the patient was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…As described, mutations for CGL patients can be homozygous or compound heterozygous, and most of the BSCL2 mutations are nonsense or frameshift mutations that are expected to cause loss of function of the protein [9]. Reports from Japan, India, China and Taiwan [9,[13][14][15][16][17][18] indicate that BSCL2 is a major causative gene for CGL in Asian (Table). However, nearly 50% of CGL cases around the world have no sequence mutation in either AGPAT2 or BSCL2 [19].…”
Section: Discussionmentioning
confidence: 99%
“…As described, mutations for CGL patients can be homozygous or compound heterozygous, and most of the BSCL2 mutations are nonsense or frameshift mutations that are expected to cause loss of function of the protein [9]. Reports from Japan, India, China and Taiwan [9,[13][14][15][16][17][18] indicate that BSCL2 is a major causative gene for CGL in Asian (Table). However, nearly 50% of CGL cases around the world have no sequence mutation in either AGPAT2 or BSCL2 [19].…”
Section: Discussionmentioning
confidence: 99%
“…Since the initial identification of BSCL2 pathogenic variants as the causes of CGL2 [Magre et al, ], there have been a number of reports of BSCL2 disease‐causing variants from European, Middle Eastern, and Asian countries [Van Maldergem et al, ; Agarwal et al, ; Shirwalkar et al, ; Rahman et al, ; Schuster et al, ; Akinci et al, ; Haghighi et al, ]. While most identified pathogenic variants are null mutations, the result of either nonsense, indel, or splicing mutations, a small number of missense variants have also been reported in CGL2 [Van Maldergem et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…It is unusual to have diabetes mellitus early in life in patients with CGL. Though metabolic abnormalities of hyperinsulinemia and insulin resistance are evident early in life, overt diabetes generally develops during the pubertal years or adulthood (5,6,7,8,17). In a report by Van Maldergem et al (5), among 24 patients with BSCL2, 16 were diagnosed to have diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a nationwide study from Turkey showed that the mean age of onset of diabetes in these patients was 16.5 years (8). CGL patients who were diagnosed as insulin resistant in infancy and who developed diabetes mellitus at puberty have also been reported (7,17). Consistently, serum insulin levels of patient 2 and patient 3 in our study were high, but they had not developed diabetes so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation